2009
DOI: 10.1007/bf03080128
|View full text |Cite
|
Sign up to set email alerts
|

Adversity does not always lead to psychopathology:cognitive reactivity is related to longitudinal changes in resilience

Abstract: A substantial majority of individuals who are exposed to a traumatic event do not develop any persistent trauma-related psychological symptoms, a phenomenon referred to as resilience. Relying on a sample of undergraduate students (n = 79), the present study investigated whether positive and negative affect and cognitive reactivity to emotional challenges serve as predictors of longitudinal changes in resilience as measured by the ConnorDavidson Resilience Scale. While at initial testing both positive affect an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 30 publications
(33 reference statements)
0
8
0
2
Order By: Relevance
“…LEIDS-r scores were found to be associated with depression history over and above rumination [36], to be associated with genetic markers of depression [23], [37], [38], and with response to tryptophan depletion, reflecting biological vulnerability to depression [22]. Moreover, treatment and other longitudinal studies support the validity of the LEIDS-r as a measure of depression vulnerability [39], [40], [41], [42].…”
Section: Methodsmentioning
confidence: 75%
“…LEIDS-r scores were found to be associated with depression history over and above rumination [36], to be associated with genetic markers of depression [23], [37], [38], and with response to tryptophan depletion, reflecting biological vulnerability to depression [22]. Moreover, treatment and other longitudinal studies support the validity of the LEIDS-r as a measure of depression vulnerability [39], [40], [41], [42].…”
Section: Methodsmentioning
confidence: 75%
“…We found a positive association between resilience and quality of life, especially within the psychosocial domain. Despite living with CRPS-I for many years and experiencing an amputation, scores on the psychosocial domain are significantly better than patients with chronic pain who visit the psychologist at a rehabilitation outpatient clinic and similar to Dutch norm values [20]. Even on the physical domain they score significantly better than the chronic pain patients.…”
Section: Crps-imentioning
confidence: 83%
“…Resilience was assessed with a Dutch version of the Connor-Davidson Resilience Scale (CD-RISC), a 25-item self-report measure that was developed to quantify current resilience [16,20]. The score ranges from 0 to 100 with higher scores indicating a better resilience.…”
Section: Questionnairesmentioning
confidence: 99%
“…Similarly, Coifman et al (2007) showed that both bereaved and nonbereaved individuals who engaged in repressive coping behaviour had fewer symptoms of psychopathology, were better adjusted and experienced fewer health problems than those who did not. In one of our recent studies, we demonstrated that cognitive reactivity to emotional challenges was predictive of a longitudinal increase in selfreported resilience (Giesbrecht et al, 2009). In the current study, we found a signifi cant correlation between cognitive reactivity and post-traumatic stress symptoms, which replicates earlier work from our lab (Giesbrecht et al, 2009).…”
Section: Discussionmentioning
confidence: 95%
“…In one of our recent studies, we demonstrated that cognitive reactivity to emotional challenges was predictive of a longitudinal increase in selfreported resilience (Giesbrecht et al, 2009). In the current study, we found a signifi cant correlation between cognitive reactivity and post-traumatic stress symptoms, which replicates earlier work from our lab (Giesbrecht et al, 2009). Moreover, because of the substantial phenomenological overlap between PTSD and depression (e.g., Rosen & Lilienfeld, 2008), our fi ndings are also reminiscent of a recent study by Booij and Van der Does (2007), demonstrating that higher levels of cognitive reactivity are a vulnerability marker of depression.…”
Section: Discussionmentioning
confidence: 95%